Pemanfaatan Augmented Reality Untuk Meningkatkan Pemahaman Kognitif Siswa Pada Materi Hewan Halal Dan Haram Di MTS Darul Amin - Muhammad Khair; Muhammad Iqbal; Akhmad Kastalani; Ahmad Aspiani; Jasiah (Cakrawala: Journal of Religious Studies and Global Society, 2025)
Students' understanding of fiqh materials, especially about halal and haram animals, is still relatively low due to the limitations of learning media that are able to provide real visualization. Augmented Reality (AR) as a technology-based interactive media is considered to have the potential to improve students' cognitive understanding through the presentation of interesting and contextual visual information. This study uses a quantitative approach with a one group pretest-posttest design. The subjects of the study were 15 students of grade VII MTs Darul Amin. The instruments used were cognitive tests given before and after learning with AR media. AR media presents halal and haram animal models in 3D form, complete with explanations of Islamic law related to each animal. The results showed an increase in the average score from 60.33 during the pretest to 79.47 during the posttest. Statistical tests using the paired sample t-test showed that the improvement was scientifically significant (p < 0.05), which indicated that the use of AR had a positive impact on students' cognitive comprehension. These findings indicate that AR-based learning media is able to increase the effectiveness of fiqh learning, especially on the topic of halal and haram animals. In addition, AR also increases student involvement in the learning process through a more interactive and visual learning experience. Thus, AR can be used as an innovative solution in the development of Islamic Religious Education learning media in the digital era.